2015
DOI: 10.1080/13546805.2015.1040151
|View full text |Cite
|
Sign up to set email alerts
|

Implicit and explicit self-related processing in relation to insight in patients with schizophrenia

Abstract: Priming with positive cues improved performance on a working memory task in patients with good cognitive insight, but worsened performance in patients with impaired cognitive insight. Furthermore, our findings suggest that the ability to adequately use feedback may be a specific capacity that is related to insight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
0
9
0
1
Order By: Relevance
“…Higher levels of self-certainty have been correlated with poorer premorbid IQ, while lower levels of self-reflectivity were linked with poorer executive function in first-episode psychosis 135 . De Vos et al 123 reported that cognitive insight was related to performance on implicit process in a working priming 2-back task and the ability to change behavior following feedback on an executive function task. Ohmuro et al 136 found that higher self-certainty was related to poorer executive function in a group at risk for psychosis.…”
Section: World Psychiatry 17:1 -February 2018mentioning
confidence: 99%
See 1 more Smart Citation
“…Higher levels of self-certainty have been correlated with poorer premorbid IQ, while lower levels of self-reflectivity were linked with poorer executive function in first-episode psychosis 135 . De Vos et al 123 reported that cognitive insight was related to performance on implicit process in a working priming 2-back task and the ability to change behavior following feedback on an executive function task. Ohmuro et al 136 found that higher self-certainty was related to poorer executive function in a group at risk for psychosis.…”
Section: World Psychiatry 17:1 -February 2018mentioning
confidence: 99%
“…Poor insight has been correlated with difficulties in set shifting in acute and non-acute phases of schizophrenia 121,122 , the ability to change behavior following feedback on an executive function task 123 , complex motor sequencing 124 , and the ability to recall autobiographical details about negative events 125 .…”
Section: Neurocognition As a Root Of Poor Insightmentioning
confidence: 99%
“…However, the present research cannot firmly establish whether the relationship between cognitive insight and neurocognition is causal , nor determine the specific mechanisms linking these variables. We propose that metacognitive awareness may be the link, as it may foster behavioral flexibility/engagement as well as the processing of corrective information (for indirect evidence to support this proposal, see de Vos et al, 2015, and Benoit et al, 2016). This hypothesis could be tested in future research by examining clinical ratings of metacognition (e.g., from the Meta-cognitive Awareness Scale–Abbreviated; Lysaker et al, 2005) as a mediating variable, along with measures of behavioral engagement (e.g., using methods such as actigraphy or ecological momentary assessment) or error/feedback processing (e.g., using event-related potentials).…”
Section: Discussionmentioning
confidence: 95%
“…The emerging literature on top-down processing provides a rationale for expecting diminished cognitive insight to contribute to the development or maintenance (i.e., etiology) of impaired neurocognition. Better cognitive insight may promote metacognitive awareness (Davies, Fowler, & Greenwood, 2017; Lysaker et al, 2011; Nicolo et al, 2012) that fosters the use of corrective feedback to improve neurocognitive performance (Benoit et al, 2016; de Vos, Pijnenborg, Aleman, & van der Meer, 2015; Lysaker et al, 2008; Nicolo et al, 2012; Reeder, Newton, Frangou, & Wykes, 2004). Furthermore, the recognition that one’s thoughts or beliefs could be inaccurate may lead an individual to seek out new information and experiences, reflected in enhanced behavioral engagement and flexibility (as opposed to disengagement and rigidity) that results in increased utilization of neurocognitive abilities (e.g., in daily activities).…”
mentioning
confidence: 99%
“…High levels of SR may encourage patients to doubt their distorted and unrealistic perceptions or thoughts, leading them to have a more-objective attitude toward their illness ( 55 ). For instance, Phalen et al ( 2 ) (p. 840) stated that “while engaged in treatment, those patients with higher cognitive insight may be better able to incorporate the feedback of mental health professionals and consider alternative ways of thinking” ( 56 ). Trials employing cognitive behavior therapy for psychosis support this theory, as they have consistently found that better cognitive insight is predictive of better responses to psychosocial treatments ( 2 , 27 ).…”
Section: Discussionmentioning
confidence: 99%